New validated eucalyptus SSR markers located in candidate genes involved in growth and plant development - Acuña, Cintia Vanesa (2020)
Aim of study: To validate and characterize new microsatellites or Simple Sequence Repeats (SSR) markers, located within genomic transcribed sequences related to growth and plant developmental traits, in Eucalyptus species. Area of study: Eucalyptus species from different Australian origins planted in Argentina. Materials and methods: In total, 134 SSR in 129 candidate genes (CG-SSR) involved in plant development were selected and physically mapped to the E. grandis reference genome by bioinformatic tools. Experimental validation and polymorphism analysis were performed on 48 individuals from E. grandis and interspecific hybrids (E. grandis x E. camaldulensis; E. grandis x E. tereticornis), E. globulus, E. maidenii, E. dunnii and E. benthamii. Main results: 131 out of 134 CG-SSR were mapped on the 11 chromosomes of E. grandis reference genome. Most of the 134 analyzed SSR (> 75%) were positively amplified and 39 were polymorphic in at least one species. A search of annotated genes within a 25 kbp up and downstream region of each SSR location retrieved 773 genes of interest. Research highlights: The new validated and characterized CG-SSR are potentially suitable for comparative QTL mapping, molecular marker-assisted breeding (MAB) and population genetic studies across different species within Symphyomyrtus subgenus.